Do students use testing and feedback while learning? A focus on key concept definitions and learning to criterion. (October 2015) - Dunlosky, John; Rawson, Katherine A.
Abstract: College students must regulate much of their learning and hence it is important to discover whether they use effective study techniques, such as testing with feedback. We conducted three experiments to evaluate the degree to which college students use testing with feedback as they are learning key concept definitions. The three main issues of interest concerned (a) whether students tested themselves during practice, (b) whether they followed tests with feedback, and (c) whether they continued to practice until they could correctly recall each definition one or more times. In each experiment, students in the self-regulated group could choose to engage in three activities (test, study, or evaluate test responses) in whatever order or dosage they wanted during practice. For purposes of comparison in each experiment, a Criterion 3 group completed an experimenter-controlled schedule of test-study practice until each definition was correctly recalled three times. All participants completed a final test one week later. Among the key outcomes, students who self-regulated their learning used tests and often sought feedback soon after. When students incorrectly recalled a definition, they typically chose to study the definition, whereas when they recalled some of a definition correctly, they typically chose to evaluate the quality of their response. Although students on average continued to test themselves until they correctly recalled each definition once, they underperformed on the final test as compared to the Criterion 3 group. Thus, in the present context, students do use testing while learning, but results also suggest that they do not take full advantage of this effective study technique. Highlights: Students must regulate a great deal of their learning. Do students use testing with feedback while studying? Students do use testing with feedback but not optimally. Students prematurely terminate practice before reaching criterion learning.